Penapisan Diabetes Melitus Melalui Pemeriksaan Kadar Gula Darah Sewaktu: Screening for Diabetes Mellitus Through Blood Sugar Level Examination - Jatmiko, Safari Wahyu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Surakarta has a population of 148,992 people living in five sub-districts, namely Laweyan, Serengan, Pasar Kliwon, Banjasari, and Jebres. Jebres District has four Community Health Centers that routinely report on diabetes mellitus (DM) health services. DM cases in the Surakarta area were 12,105 patients. The highest DM cases were in the Jebres District area, with 3,392 (27.89%) residents suffering from DM. DM cases have increased from year to year. The cause of the increase in DM cases is lifestyle changes and a lack of DM screening. The hope is that this activity can reduce the number of DM sufferers in the Jebres District area. Activities have been carried out by checking blood sugar levels at any time. The results obtained were that the blood sugar levels of study participants on Sunday morning at the Jagalan Mosque were 124.5 (47.75) mg/dL. These results indicate that blood sugar levels are still within normal limits, so in the future education and regular screening are needed to prevent cases of DM.